Adverse Events Associated with Fosfomycin Use: Review of the Literature and Analyses of the FDA Adverse Event Reporting System Database. Issue 4 (December 2015) - Iarikov, Dmitri; Wassel, Ronald; Farley, John; Nambiar, Sumathi
Abstract Introduction The growing problem of antibacterial resistance resulted in an increased interest in fosfomycin, especially its parenteral formulation. We reviewed fosfomycin safety profile using the Food and Drug Administration Adverse Event (AE) Reporting System (FAERS) and published literature. Methods We conducted a FAERS search and disproportionality analysis of all fosfomycin-associated AEs. We also conducted a FAERS search for AEs implicating fosfomycin as the primary suspect and a search of reports of fosfomycin-associated bone marrow toxicity. We then review the literature for publications reporting AEs associated with fosfomycin by conducting PubMed searches. Results The disproportionality analysis of all FAERS reports of fosfomycin-associated AEs produced a higher than expected frequency of agranulocytosis, liver injury, severe skin reactions, and pseudomembranous colitis. Subsequent search for AEs where fosfomycin was the primary suspect and the literature review did not suggest a higher association of fosfomycin with these AEs. The search of bone marrow toxicity reports did not demonstrate an association between aplastic anemia and fosfomycin. The literature review selected 23 trials of parenteral administration of fosfomycin in 1242 patients including 8 comparative and 15 non-comparative trials. For oral fosfomycin, only prospective comparative trials (n  = 28) in 2743 patients were included. The most frequent AEs associated with parenteral fosfomycin included rash, peripheral phlebitis, hypokalemia, and gastrointestinal disorders. Serious AEs such as aplastic anemia, anaphylaxis, and liver toxicities were reported infrequently. Gastrointestinal disorders were the most common AEs associated with oral fosfomycin. Conclusion The identified AEs were consistent with the safety profile of fosfomycin. No new safety signals related to either parenteral or oral fosfomycin were identified.